428. Very High Clinical Likelihood (VHCL) Of COVID-19 Infection: Peering Beyond A Negative Nasopharyngeal Swab. (31st December 2020) - Khatri, Akshay M; Flannery, Sarah; Singh, Vansha; Khameraj, Aradhana; Malhotra, Prashant; Farber, Bruce; Kast, Charles L; Gitman, Michael; Foley, Mathew; Hirschwerk, David
Abstract: Background: Diagnosis of COVID-19 relies upon RT-PCR assays for SARS-CoV-2 from a nasopharyngeal swab (NPS). However, results depend upon duration of illness at the time of testing and operator performance. False negatives occur 10–30% of the time. In our center we formulated & applied a clinical prediction tool for diagnosis of COVID-19 infection. Patients who satisfied criteria were designated as having COVID-19 regardless of NPS results. Herein, we describe the set of patients who fulfilled full and strict clinical criteria (VHCL) (Table 1) and had at least 2 negative NPSs on hospital admission. Table 1: Clinical criteria for Very High Clinical Likelihood of COVID-19 Infection (VHCL COVID-19) Methods: A retrospective descriptive study was conducted from March 4 th to April 11 th, 2020. We evaluated patients with ≥ 2 consecutive negative NPS COVID-19 results admitted to our hospital. Of these, we identified patients fitting all 5 criteria for Very High Clinical Likelihood (VHCL) of COVID-19 infection (Table 1) . We analyzed symptoms & lab data (including results of repeat NPS testing if performed) in those patients. Results: 1855 patients were diagnosed with COVID-19 in the study period. Of these, 23 had ≥ 2 negative COVID-19 NPS results but met criteria for VHCL (Table 2). Of these 23, 7 had a subsequent 3 rd NPS that was positive-proving infection. Similar to other reports, patients had low lymphocytes and elevated procalcitonin, ferritin, C-reactive protein levels. And consistent with proven cases, our cohort presented after a median of 5 days of symptoms (Table 3). Table 2: Clinical and laboratory characteristics of VHCL COVID-19 patients [Rows Bolded include those patients who had a 3rd NPS swab that was positive]. Table 3: Demographic and Median Lab Data of VHCL COVID-19 patients Conclusion: It is critical to be mindful of the imperfection of laboratory testing & to integrate clinical criteria to diagnostic algorithms. This is especially true in the COVID-19 pandemic, which is marked by high morbidity & mortality. In our study, we demonstrated how a set of clinical parameters (which we termed VHCL) can aid in widening the net of patients diagnosed with COVID-19 despite negative laboratory tests. While 16 patients in our cohort did not have a confirmatory result, the strict criteria for VHCL & the close match of other study variables with those of proven cases supports the value of VHCL designation. Applying VHCL can optimize infection control, identify patients for emerging therapeutics & aid in contact tracing to reduce nosocomial & community transmission of COVID-19. Disclosures: All Authors : No reported disclosures